2018
DOI: 10.1017/s0022215118001299
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Helicobacter pylori infection in patients with chronic rhinosinusitis with polyposis

Abstract: H pylori infection is potentially related to chronic rhinosinusitis with polyposis. Further research is needed to clarify the role of H pylori as a risk factor for the development of sinonasal diseases and to examine its link with laryngopharyngeal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…The finding of RFS > 7 was pathologically stated by Siupsinskiene in 2018. The study found a non-significant result (p=0.48) for 64.3% of CRS patients who were proven to have reflux (Siupsinskiene et al, 2018).…”
Section: Discussionmentioning
confidence: 74%
“…The finding of RFS > 7 was pathologically stated by Siupsinskiene in 2018. The study found a non-significant result (p=0.48) for 64.3% of CRS patients who were proven to have reflux (Siupsinskiene et al, 2018).…”
Section: Discussionmentioning
confidence: 74%
“…A study by Siupsinskiene et al . in this month's issue of The Journal examines the relationship between intranasal Helicobacter pylori infection and nasal polyps 7 . This work follows their previous study published last year, which demonstrated an association between H pylori infection and chronic tonsillitis and laryngopharyngeal reflux 8 .…”
mentioning
confidence: 74%
“…Six studies which provided miscellaneous data about the association between reflux and sinonasal disorders that were not formally defined as CRS were excluded. [30][31][32][33][34][35]…”
Section: Resultsmentioning
confidence: 99%